First Comparison of SARL to Other Agent-Programming Languages and Frameworks - Feraud, Maxime; Galland, Stéphane (Procedia computer science, 2017)
This paper proposes a first comparison of different agent-oriented programming languages, including the SARL agent-programming language. The study of those tools is based upon various criteria that are defining the essential aspects of multi-agent systems. For the sake of clarity, the comparative study is presented in a tabular form, including the languages and all the criteria. For each criterion, a definition is made to understand its meaning. At the end of the article, all the languages will be described in order to define their advantages and disadvantages.